2016
DOI: 10.1111/jgh.13147
|View full text |Cite
|
Sign up to set email alerts
|

Drug‐eluting beads versus conventional chemoembolization for the treatment of unresectable hepatocellular carcinoma

Abstract: In a large series of Western hepatocellular carcinoma patients, drug-eluting beads chemoembolization with 100-300 µm particles did not seem to improve survival in comparison with conventional chemoembolization, which in turn provided better tumor responses and time to progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 19 publications
2
46
2
Order By: Relevance
“…DC Beads TACE may provide improved survival rates and quality of life to some extent as compared to cTACE[32,41,47,49]. However, several RCTs and meta-analysis do not demonstrate significant survival advantages of DC Beads TACE[30,31,42].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…DC Beads TACE may provide improved survival rates and quality of life to some extent as compared to cTACE[32,41,47,49]. However, several RCTs and meta-analysis do not demonstrate significant survival advantages of DC Beads TACE[30,31,42].…”
Section: Resultsmentioning
confidence: 99%
“…There was no statistically significant difference in median OS between cTACE and DEB-TACE (11.4 mo vs 18.4 mo, respectively). Facciorusso et al[32] also reported that median survival of early/intermediate stage HCC patients ( n = 249) between cTACE and DC Beads TACE showed insignificant differences (39 mo vs 32 mo, respectively, P = 0.1).…”
Section: Survivalmentioning
confidence: 99%
See 1 more Smart Citation
“…Several consecutive sessions are usually needed for DEB-TACE to be effective, i.e ., the complete tumor response, so that the optimal treatment should lead to higher tumor necrosis rate with the lowest incidence of adverse event. DEB-TACE showed a low incidence of PES[13] and systemic toxicity than in previous reports[8], but its superiority over c-TACE is still a matter of debate[10,24-26]. …”
Section: Discussionmentioning
confidence: 99%
“…Although subgroup analysis according to the adopted TACE regimen was unfeasible due to the low number of studies, we know from previous cohort studies that DEB-TACE and cTACE lead to similar outcomes and comparable side effects in HCC patients [44, 45]. …”
Section: Discussionmentioning
confidence: 99%